2013
DOI: 10.1371/journal.pone.0075496
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Labeled n-Alkanes to Assess Digesta Passage Kinetics through the Digestive Tract of Ruminants

Abstract: We describe the use of carbon stable isotope (13C) labeled n-alkanes as a potential internal tracer to assess passage kinetics of ingested nutrients in ruminants. Plant cuticular n-alkanes originating from intrinsically 13C labeled ryegrass plants were pulse dosed intraruminally in four rumen-cannulated lactating dairy cows receiving four contrasting ryegrass silage treatments that differed in nitrogen fertilization level (45 or 90 kg nitrogen ha−1) and maturity (early or late). Passage kinetics through the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
(77 reference statements)
0
8
1
Order By: Relevance
“…Because these isotopes are present in low quantities in feed, the isotopic ratio needs to be increased in favour of the stable ( 13 C) or radioactive ( 14 C) carbon isotope relative to the main carbon isotope ( 12 C) to distinguish the marker from the bulk material. Various procedures were described for ruminant nutrition studies and include either switching from a naturally low‐C‐enriched diet based on C 3 plant species (e.g. ryegrass, lucerne, wheat) to a naturally higher‐ 13 C‐enriched diet based on C 4 plant species (e.g.…”
Section: Stable Isotopes As Digesta Passage Markersmentioning
confidence: 99%
See 4 more Smart Citations
“…Because these isotopes are present in low quantities in feed, the isotopic ratio needs to be increased in favour of the stable ( 13 C) or radioactive ( 14 C) carbon isotope relative to the main carbon isotope ( 12 C) to distinguish the marker from the bulk material. Various procedures were described for ruminant nutrition studies and include either switching from a naturally low‐C‐enriched diet based on C 3 plant species (e.g. ryegrass, lucerne, wheat) to a naturally higher‐ 13 C‐enriched diet based on C 4 plant species (e.g.…”
Section: Stable Isotopes As Digesta Passage Markersmentioning
confidence: 99%
“…the C/C ratio) may be constant between the moment of marker administration and the time of collection in the undigested faecal matter. Recent studies have shown that microbial fermentation did not affect the C/C ratio in apparent undigested material in vitro and in vivo (Ferreira LMM, unpublished) and that the 13 C/ 12 C ratio remained constant over time. Hence digestion of the labelled nutrient did not alter the isotopic ratio and its FPR in those studies.…”
Section: Stable Isotopes As Digesta Passage Markersmentioning
confidence: 99%
See 3 more Smart Citations